2010
DOI: 10.3390/ph3092799
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability Factors for the Psychiatric and Behavioral Effects of Cannabis

Abstract: Cogent evidence shows that cannabis plays a variable role on behavioral regulation and the pathophysiology of most psychiatric conditions. Accordingly, cannabis has been alternatively shown to exacerbate or ameliorate mental symptoms, depending on its composition and route of consumption, as well as specific individual and contextual characteristics. The vulnerability to the psychological effects of cannabis is influenced by a complex constellation of genetic and environmental factors. In the present article, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 210 publications
(263 reference statements)
0
7
0
3
Order By: Relevance
“…This high variability is confirmed by several preclinical studies, which have shown that anxiety-like behaviors in rodents can be either attenuated or exacerbated by Δ 9 -tetrahydrocannabinol (Δ 9 -THC), the key psychoactive ingredient of hemp, or other cannabinoids (Bortolato and Piomelli, 2008; Bortolato et al, 2010). …”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…This high variability is confirmed by several preclinical studies, which have shown that anxiety-like behaviors in rodents can be either attenuated or exacerbated by Δ 9 -tetrahydrocannabinol (Δ 9 -THC), the key psychoactive ingredient of hemp, or other cannabinoids (Bortolato and Piomelli, 2008; Bortolato et al, 2010). …”
Section: Introductionmentioning
confidence: 80%
“…Accordingly, CB 1 R agonists have been shown to exert anxiolytic or anxiogenic properties in relation to the pre-exposure to chronic stress (Hill and Gorzalka, 2004), a condition associated with CB 1 R up-regulation in the PFC and down-regulation in the midbrain (Bortolato et al, 2007). Furthermore, exposure to other substances of abuse, such as entactogens or opioids may affect the psychological outcomes of cannabinoids by altering their CB 1 R distribution (Bortolato et al, 2010; Gonzalez et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, adolescent cannabis use is associated with an increased risk of developing schizophrenia and/or accelerated onset of symptoms [5,46,47,48,49]. Emerging evidence suggests that cannabinoid exposure may have complex interactions with genetic factors associated with schizophrenia and other neuropsychiatric disorders (reviewed in [50,51]), such as the link between CNR1 gene polymorphisms and cannabinoid exposure on both brain structure and clinical outcome in schizophrenia patients [30]. By expanding this work across a variety of hiPSC-derived neurons from individuals with different schizophrenia risk alleles, we hope that our hiPSC-based model will facilitate studies of the interaction of THC exposure and genetic risk factors underlying schizophrenia vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, little is still known about the susceptibility factors that govern the behavioral outcomes of cannabis in patients affected by anxiety-spectrum disorders. Indeed, several components have been shown to play a role in this link, including genetic background, age, gender, environmental stress and concurrent use of other drugs; a detailed analysis of these determinants is outside the scope of the present work, but the interested reader should refer to [139]. …”
Section: Effects Of Cannabis and Cannabinoid Agents On Anxietymentioning
confidence: 99%